MEMBANGUN KAMUS OBSTETRI BERBASIS ANDROID (Studi Kasus : Kampus Kebidanan Adila Bandar Lampung) - Yuni Puspita Sari (Jurnal Informatika, 2016)
The today’s learning process is greatly influenced by student’s memory. In learning obstetrics, the delivery of learning material using guidebook still used old learning method where the obstetrics students have to understand the material delivered by the lecturer. Besides, by using the guidebook, the users have to look up the meanings of obstetric words manually, without any pronunciation model. It is even very difficult to bring the book and to update as to the needs and current development. Therefore, it is needed the availability of obstetric dictionary that can make it easy for the people to look up the obstetric terminology easily and quickly. The application of obstetric dictionary is an application made for the development method that was prototype that expects the obstetrics students to learn the obstetric glossary more easily. The prototype method has several phases, namely: needs collection, design and prototype evaluation. It can also test the prototype and the built application to solve problems. This study was done to result in an android-based application of obstetrics dictionary which can facilitate the learning process to the students and the users. This application can help understanding and pronouncing terminologies of obstetrics well. Keywords : Dictionary, Obstetrics, Prototype, Android.